KEPENTINGAN STRATEGIS MINYAK BUMI DALAM ESKALASI KONFLIK AMERIKA SERIKAT DAN IRAN - Satryo Pringgo Sejati; Ahmad Burhan Hakim (JOSH: Journal of Sharia, 2026)
This study discusses the strategic interests of petroleum in the escalation of conflict between the United States and Iran from the perspective of international relations. The conflict between the two countries represents one of the most complex geopolitical dynamics in the Middle East, influenced not only by ideological and security issues but also by global energy interests. Iran, as one of the countries with the largest oil reserves in the world, holds a strategic position in international energy distribution, particularly through the Strait of Hormuz, which serves as a major route for global oil trade. This condition places Iran as an important actor in energy geopolitics and a central concern of United States foreign policy.This research employs a qualitative method with a descriptive-analytical approach and utilizes library research as the primary research design. Data were collected from official documents, scientific journals, books, academic articles, and various international media sources related to the conflict between the United States and Iran. The analysis applies realism theory and an energy geopolitics approach to explain the relationship between national interests, control over energy resources, and the escalation of international conflict.The results of the study indicate that petroleum is a major factor influencing the dynamics of relations between the United States and Iran. The United States seeks to maintain its geopolitical dominance and global energy stability through various political and economic policies toward Iran, while Iran utilizes its energy resources and strategic geographical position to preserve its regional influence and national sovereignty. The conflict between the two countries demonstrates that oil is not merely an economic commodity but also a strategic political instrument in the struggle for global power. In addition to affecting the stability of the Middle East region, the US–Iran conflict also has significant implications for global energy security and the international economy